Progress and prospectus in genetics and genomics of Phytophthora root and stem rot resistance in soybean (Glycine max L.) - Chandra, Subhash; Choudhary, Mukesh; Bagaria, Pravin K.; Nataraj, Vennampally; Kumawat, Giriraj; Choudhary, Jeet Ram; Sonah, Humira; Gupta, Sanjay; Wani, Shabir Hussain; Ratnaparkhe, Milind B. (Frontiers in Genetics, 2022)
Soybean is one of the largest sources of protein and oil in the world and also being considered as ‘super crop’ due to several industrial advantages. However, enhanced acreage and adoption of the monoculture practices rendered the crop vulnerable to several diseases. Phytophthora root and stem rot (PRSR) caused by Phytophthora sojae is one of the most important diseases adversely affecting soybean production globally. Deployment of genetic resistance is the most sustainable approach for avoiding the yield losses due to this disease. PRSR resistance is complex in nature and difficult to address by the conventional breeding alone. Genetic mapping through the cost-effective sequencing platform facilitates the identification of candidate genes and associated molecular markers for genetic improvement against PRSR. Further, with the help of novel genomic approaches identification and functional characterization of Rps (“resistance to Phytophthora sojae”) was also progressed in the recent past and more than 30 Rps genes imparting complete resistance against different PRSR pathotypes have been reported. Besides, many genomic regions imparting partial resistance also have been identified. Furthermore, the adoption of emerging approaches like genome editing, genomic-assisted breeding and genomic selection etc. can assist in the functional characterization of novel genes and their rapid introgression for PRSR resistance. Hence, in the near future, soybean growers will likely witness an increase in production by adopting PRSR resistant cultivars. This review highlights the progress made in deciphering the genetic architecture of PRSR resistance, genomic advances and future perspectives for the deployment of PRSR resistance in soybean for sustainable management of PRSR disease.